Penerapan Model Rapid Application Development Dalam Pembuatan Sistem Informasi Akuntansi Penjualan Dan Pembelian Berbasis Web - Dharmawan, Weiskhy Steven; Dharmawan, Weiskhy (LPPM Universitas Bina Sarana Informatika, 2025)
The system currently used for residential sales and purchases relies mainly on paper media, which is then transcribed into Microsoft Excel. This practice affects the process and accuracy of report presentation. Therefore, this Final Project discusses the design and development of an accounting information system for residential sales and purchases using rapid application development as a software development model. This model includes business modeling, data modeling, process modeling, application creation, and testing. Data collection techniques include interviews, observations, and literature studies. The system provides facilities for two levels of users: admin and director. The admin can manage account data, land, houses, consumers, purchase transactions, land sales, house sales, expenses, and access reports on land inventory, house inventory, sales, purchases, and expenses. The director can manage user data, access reports on land inventory, house inventory, sales, purchases, expenses, general journals, ledgers, trial balances, income statements, and statements of changes in equity. The system is built using Hypertext Preprocessor (PHP) as the programming language, Laravel as the framework, and SQLYog as the database application. This application is expected to assist in managing sales and purchase transactions and generating reports according to needs.